Factors Influencing Job Promotion in Iranian Nursing Profession, Barriers and Facilitators - Fatemeh Mirmohammadi; Mohammad Ali Shah Hoseini; Hamid Reza Yazdani; Abbas Ebadi (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Job promotion is one of the most important issues in nursing profession. Objectives: Although, it is more than one hundred years since the beginning of modern nursing education in Iran, numerous challenges still exist in professional promotion of clinical nurses. Barriers and facilitators of job promotion are important factors that should be considered for the individual development of nurses and efficiency increase of healthcare organizations. This study aims to identify and present factors influencing, barriers and facilitators of nursing job promotion in Iran. Methods: This qualitative study was conducted in 2017 using individual semi-structured interviews with twenty-two experts in health and nursing management. The data were analyzed using content analysis based on Graneheim and Lundman method. The main questions of the interview included the following: -How is nursing job promotion done in your organization?‖ and -What are the barriers and facilitators of job promotion for nurses?‖ Results: The findings were categorized into six themes and ten categories. Facilitators for job promotion among nurses included: development of an atmosphere for mutual growth and excellence, lifelong training program, exploring professional identity in healthcare team & society and fair compensation for the services, salaries and benefits. Meanwhile, wrong cultural beliefs and barriers, ineffectiveness organizational regulations were some barriers of nursing job promotion. Conclusion: Nurses' motivation is fluctuating due to empowering factors and barriers. Health systems certainly can institutionalize and perform nursing job promotion solutions through short and long-term planning on job promotion (such as compensation for the services, encouragement for nurses, organizational culture improvement, atmosphere change in society and organizational).